Protection in Good and Bad Times? The Turkish Green Card Health Program - Aran, Meltem A.; Hentschel, Jesko S. (2013)
This paper evaluates the equity and financial protection implications of the expansion of the Green Card (Yesil Kart) non-contributory health insurance program in Turkey during the growth years from 2003 to 2008. It also considers the program's protective impact during the economic crisis in 2009. The authors find that the rapid expansion of the program between 2003 and 2008 was highly progressive. It led to significant gains in coverage of the poor but offered limited financial protection as out-of-pocket expenditures even before the introduction of the program had been limited. Using a specialized welfare monitoring survey, fielded in 2009, the authors estimate the impact of the program on household level health care utilization during the first phase of the economic slowdown in Turkey. Using three different estimation techniques, they find that the Green Card program had a significantly positive impact on protecting health care utilization during the crisis.